2021
DOI: 10.1186/s43163-021-00158-x
|View full text |Cite
|
Sign up to set email alerts
|

A common symptom with an uncommon diagnosis

Abstract: Background Nasopharyngeal carcinoma is one of the uncommon tumours and the most difficult tumour to diagnose at an earlier stage due to the clandestine and deceptive nature. The incidence is more common in men with a peak incidence of 50 to 60 years. The suspicion of tumour at the earliest stage is very helpful in reducing morbidity and mortality. Case presentation A 45-year-old female presented with right hemi cranial headache for 2years without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Wu et al have found that those who present only with headaches had the highest misdiagnosis rate of 86.4% among patients with nasopharyngeal cancer [19]. Velayutham et al reported a case of a 45year-old female that presented with a right hemicranial headache for two years and was diagnosed later to have an NPC [20].…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al have found that those who present only with headaches had the highest misdiagnosis rate of 86.4% among patients with nasopharyngeal cancer [19]. Velayutham et al reported a case of a 45year-old female that presented with a right hemicranial headache for two years and was diagnosed later to have an NPC [20].…”
Section: Discussionmentioning
confidence: 99%
“…These 4 signals are: 1) the interaction between T cell receptor (TCR) on the T cells and MHC; 2) co-stimulation through CD28 and CD80/86, which are expressed on T cells and DC respectively; 3) secreting pro-inflammatory cytokines such as interferon (IFN) and interleukin (IL)-12, which can stimulate the expansion function and memory formation of CTL; or 4) DC control the activation of particular integrins and chemokine receptors on T cells to guide migration in the direction of targeted organs. [13][14][15][16][17][18] After being activated by DC, CTL cells will secrete the cytolytic granzyme B that can effectively induce rapid apoptosis of target cells. On the other hand, DC also secrete several cytokines and a large number of exosomes, which together operate as a whole antigen-presenting entity.…”
Section: Vaccine For Cancermentioning
confidence: 99%
“…Patients with nasopharyngeal carcinoma may present with symptoms mimicking a prolonged common cold and/or otitis media; a high degree of suspicion by clinicians can prompt early referral to ENT for proper treatment. 1,2 • Incorrect imaging. For example, functional endoscopic sinus surgery (FESS) for nose and sinus issues requires image-guidance CT scans of the sinuses.…”
Section: Review Articlementioning
confidence: 99%
“…Patients with sudden sensorineural hearing loss (SNHL) need urgent referral to ENT for intratympanic corticosteroid injection or high-dose oral corticosteroid therapy to restore the patient's hearing. Patients with nasopharyngeal carcinoma may present with symptoms mimicking a prolonged common cold and/or otitis media; a high degree of suspicion by clinicians can prompt early referral to ENT for proper treatment 1,2…”
mentioning
confidence: 99%